Ligas multicomponentes produzidas a partir de cavacos de Ti e/ou materiais com pureza comercial para armazenagem de hidrogênio - Ferraz, Mariana de Brito
This work aims to investigate multicomponent alloys for hydrogen storage through the formation of metal hydrides, using titanium alloy scrap (Ti Grade 2 – ASTM F67 and Ti6Al4V-ELI – ASTM F136) and commercially pure metallic elements, with the goal of obtaining more sustainable materials in terms of the environmental impact of raw materials. Initially, the Ti-V-Nb-Cr system was studied by replacing high-purity Ti with Ti6Al4V-ELI scrap, resulting in the Ti18Nb23V24Cr33Al2 alloy, whose major phase exhibits a body-centered cubic (BCC) structure. The presence of Al and the lower Ti content increased the equilibrium pressure and reduced hydride stability compared to the reference alloy (TiVNb)65Cr35, produced from high-purity elements. Nevertheless, the recycled alloy showed a hydrogen storage capacity of 2.7 wt.% H at room temperature and improved cyclic stability. To further reduce the carbon footprint, vanadium was eliminated from the composition, as primary V presents the highest CO2-equivalent emissions in the Ti-V-Nb-Cr system. Alloys from the T-Nb-Cr system were then developed using Ti Grade 2 and Ti6Al4V-ELI scrap. The Ti33Nb33Cr33 and Ti32Al2V1Nb37Cr28 alloys exhibited predominantly BCC microstructures, with a fraction of C15Laves phase, and hydrogen storage capacities between 2.25 and 2.5 wt.% H. CO2 emissions associated with raw materials were reduced by approximately 30% after removing V from the composition. Finally, the Ti15Zr17Fe22Mn21Cr22Al2V1 alloy, produced from Ti6Al4V-ELI scrap and commercial elements, was investigated. This alloy formed a C14 Laves phase and exhibited a hydrogen storage capacity of 1.2 wt.% H, with excellent reversibility at room temperature. Despite the lower capacity, the emissions associated with its raw materials were only 1.3 kg CO2-eq, corresponding to reductions of 89% and 80% compared to the Ti-V-Nb-Cr and Ti-Nb-Cr systems, respectively.